2015
DOI: 10.1089/scd.2014.0397
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Inhibits Embryonic Stem Cell Self-Renewal and Neural Differentiation ThroughmiR-9/E-cadherinSignaling

Abstract: The commonly used inhalation anesthetic, isoflurane, can permeate rapidly through the placental barrier and thus cause toxicity to the central nervous system of the developing fetus. In this study, we treated pregnant mice with clinically relevant concentration of isoflurane early on in development (days 3.5-6.5), and then found that the fetus growth was inhibited by isoflurane. We further used the mouse embryonic stem cell (mES cell) to be the early development model to investigate the mechanism of the embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Researchers endeavor to manipulate the expression of particular miRNAs in order to promote stem cells differentiation into neural progenitor cells or authentic neural cells282930. In this study, we analyzed miRNA expression profiling that significantly changed when ASCs were treated with RA for neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers endeavor to manipulate the expression of particular miRNAs in order to promote stem cells differentiation into neural progenitor cells or authentic neural cells282930. In this study, we analyzed miRNA expression profiling that significantly changed when ASCs were treated with RA for neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the neural differentiation of mESCs by using the methods described in previous studies 33,34 . The detail of the neural differentiation is as follows: we performed neural differentiation studies by using 46c mouse embryonic stem cells (mESCs).…”
Section: Methodsmentioning
confidence: 99%
“…After the NSCs were washed 3–4 times (5 min each) with PBS, nuclei were counterstained with DAPI (Vectorlabs, Burlingame, CA, USA). Finally, the cells were mounted onto glass slides and imaged using a laser-scanning confocal microscope (Olympus FV10i, Tokyo, Japan) for cell counting using previously described protocols [ 24 ]. Briefly, nuclei were counted in five fields per well (center and at the 3, 6, 9, and 12 o’clock positions).…”
Section: Methodsmentioning
confidence: 99%
“…MiR-137, miR-124, miR-34a, and miR-34c have also been implicated in ketamine-induced neurotoxicity in various in vivo and in vitro models [ 20 – 23 ]. Recently, miR-9 was shown to be involved in the inhibition of embryonic stem cell self-renewal and neural differentiation following exposure to the inhaled anesthetic isoflurane [ 24 ]. Another investigation also indicated that anxiety-like disorders caused by postnatal exposure to sevoflurane may be related to miR-632, which targets BDNF and a voltage dependent calcium channel [ 25 ].…”
Section: Introductionmentioning
confidence: 99%